The impact of outpatient settlement for cross-regional medical treatment on healthcare choice by the floating population: PSM+DID evidence based on CFPS - Qiang Su; Yumeng Zhang; Yuanhao Sui; Lihua Sun; Dawei Zhang (PLoS ONE, 2025)
The issue of regional disparities in medical resources and insurance benefits is notably prevalent in China. As a result, seeking medical treatment across regions has emerged as a focal point of health reform efforts in recent years. This study examines the impact of outpatient settlement for cross-regional medical treatment on healthcare choices by the floating population who live and work in regions different from their registered residence. Using data from the China Family Panel Studies (CFPS), this study conducts an empirical analysis through Propensity Score Matching and Difference-in-Differences (PSM + DID). The analysis included a sample of 3,019 floating population from 2012 to 2020. The findings indicate that they are significantly more inclined to select advanced medical institution (coefficient = 0.252, p < 0.05) due to the influence of the policy. Furthermore, heterogeneity analysis reveals that this policy primarily affects the labor force (coefficient = 0.268, p < 0.05) and urban residents (coefficient = 0.286, p < 0.05) within the floating population. Ultimately, the outpatient settlement for cross-regional medical treatment affects the floating population to seek care at advanced medical institution, which conflicts with the objectives of the hierarchical medical system. Policymakers should enhance communication to ensure better coordination between these policies.